2014
DOI: 10.1136/bjophthalmol-2014-305047
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic parameters in uveal melanoma and their association with BAP1 expression

Abstract: Aim To determine whether BAP1 gene and protein expression associates with different prognostic parameters in uveal melanoma and whether BAP1 expression correctly identifies patients as being at risk for metastases, following enucleation of the primary tumour. Methods Thirty cases of uveal melanoma obtained by enucleation between 1999 and 2004 were analysed for a variety of prognostic markers, including histological characteristics, chromosome aberrations obtained by fluorescence in situ hybridisation (FISH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 45 publications
(28 reference statements)
3
84
1
2
Order By: Relevance
“…A flat or nodular black gray mucosal lesion is most often identified on the palate or gingiva [8,9,17,18]. Lesions are often detected by the patient or on oral [2,3] Cutaneous [4,5] Ocular (uveal) [6] examination during a dental procedure and require differentiation from amalgam tattoos: metal "pigment" from prior dental work accumulating in macrophages. Up to 1/3 of lesions may show ulceration.…”
Section: Oral Cavitymentioning
confidence: 99%
“…A flat or nodular black gray mucosal lesion is most often identified on the palate or gingiva [8,9,17,18]. Lesions are often detected by the patient or on oral [2,3] Cutaneous [4,5] Ocular (uveal) [6] examination during a dental procedure and require differentiation from amalgam tattoos: metal "pigment" from prior dental work accumulating in macrophages. Up to 1/3 of lesions may show ulceration.…”
Section: Oral Cavitymentioning
confidence: 99%
“…More recently, mutations occurring in UM have been identified in several genes, including GNAQ , GNA11 , BAP1 , SF3B1 , EIF1AX , PLCB4 , and CYSLTR2 11, 18, 19, 20, 21, 22. In particular, inactivating BAP1 mutations are associated with a poor outcome, being present in ∼84% of all UMs that went on to produce metastases 19, 23, 24. BAP1 mutations similarly correspond with a significantly worse prognosis in renal clear cell carcinoma 25 and cholangiocarcinoma 26, whilst in mesothelioma BAP1 inactivation is associated with a good prognosis 27.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown promising results, in particular an excellent correlation of BAP1 immunostaining with genetic analysis (although in some cases discrepancies were observed) [1,3,4], as well as the identification of a subgroup of "atypical" poor-prognosis disomy 3 patients [2]. Thus, BAP1 immunohistochemical screening was suggested as the routine staining for UM molecular work-up [2,3].…”
Section: Disclosure Statementmentioning
confidence: 99%
“…Recently, its prognostic role in uveal melanoma (UM) has been further elucidated by several independent groups showing that somatic BAP1 mutations are associated with a higher risk for metastasis [1][2][3][4][5]. While genetic testing is expensive and time-consuming, immunohistochemical staining can be easily performed on formalin-fixed paraffin-embedded tissue, and was therefore proposed as a good alternative [3].…”
Section: Disclosure Statementmentioning
confidence: 99%
See 1 more Smart Citation